PENGGUNAAN PUPUK SUPER BIONIK PADA PERTUMBUHAN ANGGREK DENDROBIUM - Made, Usman (AgriSains, 2009)
ABSTRACT The research aim was to study the growth of Dendrobium applied with various concentrations of super bionik fertilizer. The research conducted used a Randomized Block Design consisting of 6 treatments: without super bionik fertilizer, 1 ml super bionik fertilizer/l water, 2 ml super bionik fertilizer/l water, 3 ml super bionik fertilizer/l water, 4 super bionik fertilizer ml/l water, 4 ml super bionik fertilizer/l water, and super bionik fertilizer 5 ml/l water. Each treatment was replicated 3 times. Data were analyzed using ANOVA and HSD at 5 %. The research results showed that the application of super bionik fertilizer significantly increased plant height and leaf number but no significant effect on the number of buds. The application of super bionic fertilizer at concentration of 4 ml/l water showed greater plant height and number of leaf than the other concentrations.